2018
DOI: 10.1093/jxb/ery360
|View full text |Cite
|
Sign up to set email alerts
|

Phytophthora infestansRXLR effectors act in concert at diverse subcellular locations to enhance host colonization

Abstract: Fifty-two infection-induced Phytophthora infestans RXLR effectors have diverse subcellular localizations, and the majority significantly enhance infection when expressed in leaves. Combining effectors targeting different defence pathways additively enhances colonization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
109
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(122 citation statements)
references
References 64 publications
10
109
1
2
Order By: Relevance
“…However, it remains unclear whether these two IRs are required for interaction (if any) between PlAvh142 and its target protein(s) in the plant cells. RXLR effectors could localize in different compartments of the host cells, in correspondence to their various molecular/cellular functions during the host-pathogen interaction (Liu et al, 2018;Wang et al, 2019a). Thus, perception of effector proteins by the cognate receptor(s) is frequently associated with their localized position, for example activation of R1-mediated HR and resistance required localization of the R1/AVR1 pair in the nucleus, although both AVR1 and its cognate R protein R1 could be observed in cytoplasm and nucleus (Du et al, 2015).…”
Section: Plavh142 Contributes To P Litchii Virulencementioning
confidence: 99%
See 1 more Smart Citation
“…However, it remains unclear whether these two IRs are required for interaction (if any) between PlAvh142 and its target protein(s) in the plant cells. RXLR effectors could localize in different compartments of the host cells, in correspondence to their various molecular/cellular functions during the host-pathogen interaction (Liu et al, 2018;Wang et al, 2019a). Thus, perception of effector proteins by the cognate receptor(s) is frequently associated with their localized position, for example activation of R1-mediated HR and resistance required localization of the R1/AVR1 pair in the nucleus, although both AVR1 and its cognate R protein R1 could be observed in cytoplasm and nucleus (Du et al, 2015).…”
Section: Plavh142 Contributes To P Litchii Virulencementioning
confidence: 99%
“…After being secreted by oomycetous pathogens, the RXLR effectors are transported to a range of subcellular localizations in plant cells, including the nucleus, cytoplasm, or plasma membrane, which often associates with their functions and/or mode of action (McLellan et al, 2013;Xiang et al, 2016). The study of subcellular localization of RXLR effectors from Phytophthora infestans revealed that the nucleocytoplasmic distribution in plant cells is the most common pattern (Wang et al, 2019a). P. sojae Avh238 triggers cell death when it is present in the nucleus .…”
mentioning
confidence: 99%
“…The time course suggests that Pi22926 contributes to the biotrophic phase of infection, similar to other PiRXLR effectors (Whisson et al, 2016). Recently, Pi22926 was shown to be secreted from P. infestans haustoria and delivered into host cells to accumulate in the nucleus (Wang et al, 2018), where it enhances P. infestans colonization of N. benthamiana (Wang et al, 2019). We confirmed that the disease lesion diameters on the half leaves transiently expressing GFP-Pi22926 (the signal peptide was deleted) were significantly larger compared to the GFP control 6 d postinoculation (dpi; Supplemental Fig.…”
Section: Resultsmentioning
confidence: 93%
“…A mitogenactivated kinase, Crk1, transported in early endosomes is involved in the retrograde signaling that coordinates effectors expression. Wang and colleagues have used fusion to fluorescent proteins and heterologous expression in the model host Nicotiana benthamiana to identify the subcellular targets of 52 Phytophthora infestans effectors (Wang et al, 2019). While most of these effectors are nucleocytoplasmic, many others target more specific localizations, including the plasma membrane, the ER, microtubules or host organelles such as the nucleus, indicating the vast diversity of host subcellular compartments targeted by the pathogen and, consequently, indicating where host molecular interactors might be located.…”
Section: In Fungi Size Matters: Plant Pathogens Possess the Largest Smentioning
confidence: 99%